Gadget Ini Membunuhmu: Urgensi Penyadaran atas Fenomena Problem Pendidikan Islam - Robingun Suyud El Syam; Ali Mutafi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This article focuses on the aim of exploring the urgency of raising awareness of healthy living culture towards the phenomenon of gadget addiction, by specifying the connection to Islamic education. The research is the result of findings from qualitative literature research, with an awareness theory approach which is then drawn on the urgency of learning culture. The research results conclude: Islamic education focuses on training cells to become intelligent again, so that they can reach their natural potential through special physical training so that gadget addiction needs to be diverted to positive activities. Research recommends strengthening self-awareness as a solution to gadget addiction. This action minimizes the risk of disease and learning disorders. Research is expected to contribute to the world of Islamic medicine and education.